Shallot Agrotourism Based on Local Resources (Mulch and Organic Fertilizer) to Achieve Sustainable Agroecosystem in Sigerongan Village - A. Farid Hemon; Tufaila Hemon; Endah Wahyuningsih; Lestari Ujianto; Dwi Putra Buana Sakti (Unram Journal of Community Service, 2025)
The Farming in Sigerongan village is highly intensive, potentially leading to chemical residues such as pesticides and fertilizers, which pose a problem for the biological, physical, and chemical balance of the soil and the environment. Sigerongan village, with its "Sumber Hidup" Farmers Group, is a popular destination for local tourism, necessitating the development of a farming system that is both economically valuable and environmentally friendly. Shallot farming offers an alternative for developing agrotourism through the use of local resources such as rice mulch and organic fertilizer. Researchers have collected several superior shallot varieties and utilized mulch and manure to increase the productivity of small plots. To achieve this goal, direct extension activities and demonstration plots (action research) have been conducted with farmers. The training method used is adult education (POD) using participatory techniques. These activities aim to improve the skills and knowledge of partner farmers. The results of the activity showed that the development of shallot agrotourism based on local resources has been carried out in the "Sumber Hidup" farmer group in Sigerongan village. Partner farmers have been very responsive to the community service activities. The technological transformation process of using rice straw mulch and cow manure in shallot cultivation has been implemented. Partner farmers are expected to experience behavioral changes in knowledge, skills, and attitudes to develop shallot agrotourism. 3. The chemical-free shallot cultivation technique that has been developed has the potential to promote agrotourism in Sigerongan village.